The effect of foot exercise on increasing sensitivity and blood sugar in type 2 diabetes - Riskawaty, Heny Marlina (Institute Of Computer Science (IOCS), 2025)
Diabetes Mellitus is a chronic metabolic disorder caused by many factors such as high blood sugar levels resulting from impaired insulin function. Diabetic foot exercises is exercises that can doing with moving the muscles and joints of the feet, improving blood circulation, strengthening small muscles, preventing foot deformities. The monofilament test is a tool to check for nerve damage (peripheral neuropathy), caused by conditions such as diabetes mellitus. Temporary blood glucose is a check of glucose levels in non-fasting blood that can be done at any time. Objective: To determine the effect of diabetic foot exercises toward foot sensitivity and blood sugar levels on diabetes mellitus type 2 patients at Dasan Lekong Public Health Center, East Lombok. Method: The design of this research is quasi-experimental research with a pretest-posttest with control group design. The population in this study was 45 people. While the sample in this study was 18 people. Results: Using the Wilcoxon test, there was an effect of diabetic foot exercises toward foot sensitivity on diabetes mellitus type 2 patients with a p value (0.000) < a (0.05). Likewise, there is an effect of diabetic foot exercises toward blood sugar levels with p (0.000). Conclusion: There is an effect of diabetic foot exercises on increasing foot sensitivity and blood sugar levels on diabetes mellitus type 2 patients.